Seismic Performance Assessment of an Ultra-High–Voltage Power Transformer. Issue 1 (February 2019) - Ma, Guo-Liang; Xie, Qiang; Whittaker, Andrew
Ultra-high–voltage (UHV) power distribution systems are seeing increased use in the seismically active regions of developing world, including China, as backbone power grids are being built out over long distances. This paper presents a study of the seismic performance of a UHV power transformer. Construction details for a typical Chinese UHV power transformer are described. The seismic behavior of the UHV power transformer is evaluated numerically, including calculation of modal properties and response to design basis earthquake shaking. The amplification of ground motion to the points of attachment of the seismically vulnerable transformer bushings is characterized. Alternative configurations for the sidewall-mounted turrets are investigated to mitigate the dynamic response of the 1, 100-kV bushing.